2016
DOI: 10.1021/acs.inorgchem.5b02962
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and Efficient White Light Phosphorescent Emission Based on Single Component N-Heterocyclic Carbene Platinum(II) Complexes

Abstract: A new class of cyclometalated pyridine N-heterocyclic carbene (NHC) Pt(II) complexes with electronically different alkyne derivatives (C≡CR; R = C6H4C(CH3)3 (1), C6H5 (2), C6H4F (3), C6H3(CF3)2 (4)) as ancillary ligands were synthesized, and the consequences of the electronic properties of the different substituted phenylacetylene ligands on the phosphorescent emission efficiencies were studied, where C≡CC6H4C(CH3)3 = 4-tert-butylphenylacetylene, C≡CC6H5 = phenylacetylene, C≡CC6H4F = 4-fluorophenylacetylene, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 72 publications
5
50
0
Order By: Relevance
“…It reveals that at the concentration of 20 wt% in poly(methyl methacrylate) (PMMA), both complexes 37 and 38 possess the CIE coordinates close to the pure white light (x = 0.33, y = 0.33). [89] Like the Pt(II) complexes, the gold(I)···gold(I) (Au(I)···Au(I)) interaction to achieve the white-light emission is possible due to the strong tendency to form the excimer, which is supported by the rigid planar configuration and linear coordination mode of Au(I) complexes. [90,91] In 2013, Li et al reported a trinuclear Au(I) cluster 40 which shows a clear dual emission at around 450 nm of the HE side and 560 nm of the LE side in degassed CH 2 Cl 2 at a concentration of 10 −3 m, with the CIE coordinates of (x = 0.28, y = 0.29) and a quantum yield of 25.9%.…”
Section: Excimers In Transition Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…It reveals that at the concentration of 20 wt% in poly(methyl methacrylate) (PMMA), both complexes 37 and 38 possess the CIE coordinates close to the pure white light (x = 0.33, y = 0.33). [89] Like the Pt(II) complexes, the gold(I)···gold(I) (Au(I)···Au(I)) interaction to achieve the white-light emission is possible due to the strong tendency to form the excimer, which is supported by the rigid planar configuration and linear coordination mode of Au(I) complexes. [90,91] In 2013, Li et al reported a trinuclear Au(I) cluster 40 which shows a clear dual emission at around 450 nm of the HE side and 560 nm of the LE side in degassed CH 2 Cl 2 at a concentration of 10 −3 m, with the CIE coordinates of (x = 0.28, y = 0.29) and a quantum yield of 25.9%.…”
Section: Excimers In Transition Metal Complexesmentioning
confidence: 99%
“…The white emissions are due to the blue emissions at around 460–490 nm from Pt(II) monomers and the excimeric emissions at about 580 nm due to MMLCT with the increased Pt(II) concentration in films. It reveals that at the concentration of 20 wt% in poly(methyl methacrylate) (PMMA), both complexes 37 and 38 possess the CIE coordinates close to the pure white light ( x = 0.33, y = 0.33) …”
Section: White‐light Emission Based On Single Organic Moleculesmentioning
confidence: 99%
“…[6][7][8] Currently, most blue-emitting materials with high quantum yield are based on Ir(III) as the 1 metal ion, but the number of Pt(II) compounds is increasingly growing. 3,[9][10][11][12][13][14][15][16] Population of a high energy excited state required for an efficient blue emission upon excitation competes with the photo-or thermal population of high-lying metal dd* states, the later leading to severe geometrical distortions of the molecules which result in non-radiative deactivation and degradation via bond-breaking processes. 17 In the chemistry of Pt(II), a common approach for the design of efficient and stable blue-phosphorescent systems is the incorporation of strong field 7 ligands to the metal coordination sphere, such as C-deprotonated imines able to act as 8 bidentate, 18,19 tridentate 11,17,20 and even tetradentate [21][22][23][24] ligands.…”
Section: Extensive Investigations On Phosphorescent Transition Metal mentioning
confidence: 99%
“…However, the luminescent properties might be changed by making the film depending on the complexes. 27,28) Therefore, it is desirable to develop a copper(I)-halide complex, in which the original luminescent properties of the powder are retained even in film state. Among the polymers used as binding agents, polymethyl methacrylate (PMMA) is preferred, because it is highly transparent, light-resistant, and easily forms a thin film.…”
Section: Introductionmentioning
confidence: 99%